Ultrafast Dynamic Piezoresistive Response of Graphene‐Based Cellular Elastomers. Issue 1 (2nd November 2015) - Qiu, Ling; Bulut Coskun, M.; Tang, Yue; Liu, Jefferson Z.; Alan, Tuncay; Ding, Jie; Truong, Van‐Tan; Li, Dan
Abstract : Ultralight graphene‐based cellular elastomers are found to exhibit nearly frequency‐independent piezoresistive behaviors. Surpassing the mechanoreceptors in the human skin, these graphene elastomers can provide an instantaneous and high‐fidelity electrical response to dynamic pressures ranging from quasi‐static up to 2000 Hz, and are capable of detecting ultralow pressures as small as 0.082 Pa.